PEDAGOGICAL CONDITIONS OF SUCCESSFUL FORMATION COMMUNICATIVE SKILLS IN FUTURE TEACHERS TECHNOLOGIES IN EDUCATION OF STUDENTS’ LOVE FOR WORK - Gura Л.В. (Pedagogy of Higher and Secondary Education, 2022)
In classe (article) pedagogical problems of successful Jormation communicative skills the teacher of technology due to what in pupils will be fixed and improve knowledge and practical skills that will enable to realize their creative individuality are opened.